IMPLEMENTASI MODEL PENEMUAN TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP NEGERI 10 MEDAN - Sitorus, Pricilia Mawar M; Hasratuddin, Hasratuddin (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
The aim of this study is to enhance the students' ability to solve math problems and classical completeness of students in grade VIII SMP Negeri 10 Medan through Guided Discovery Learning model. This research is called Classroom Action Research (CAR) and carried out by two cycles, where each cycle includes the stages of planning, implementation, monitoring, evaluation and reflection. The research subjects were 32 students of grade VIII-C SMP Negeri 10 Medan T.A 2023/2024. The object of this study is to enhance the math problem solving capability of students by applying the Guided Discovery Learning model on chance material. The results obtained from the initial ability test before applying the learning model that the average student score was 40.19. In cycle I, there was an increase with the average student score of 66.21 which was in the moderate category and there were 16 students (50%). Then in cycle II it increased with an average student score of 85.29 which is in high category and 29 students (90.62%). Thus the conclusions that can be drawn from this is the Guided Discovery Learning model can enhance the ability of students in grade VIII SMP Negeri 10 Medan to solve problems of math